Taxes and Trust From Coercion to Compliance in Poland, Russia and Ukraine - Berenson, Marc P. (Cambridge University Press, 2018)
Taxes and Trust is the first book on taxes to focus on trust and the first work of social science to concentrate on how tax policy actually gets implemented on the ground in Poland, Russia and Ukraine. It highlights the nuances of the transitional Ukraine case and explains precisely how and why that 'borderland' country differs from the more ideal types of coercive Russia and compliance-oriented Poland. Through eight bespoke taxpayer surveys, an unprecedented survey of bureaucrats and more than fifteen years of qualitative research, it emphasizes the building and accumulation of trust in the transition from a coercive tax state to a compliant one. The content of the book will appeal to students and scholars of taxation worldwide and to those who study Russia and Eastern Europe.